(untitled) (Research, Society and Development, 2020)
Pig farming has received a strong increase, with the introduction of new techniques and has been growing strongly in Brazil and in the world. According to the Brazilian Animal Protein Association, Brazil ranks 4th as the largest pork producer and exporter. These data show that in the swine production system, the owner has an extreme importance in the area, which correct management in all stages of creation bring positive results, as well as losses in production with regard to incorrect handling. Consumers are increasingly aware of animal welfare, with this requirement being among the main requirements. The environment must be clean and dry and with proper handling of the channels in order to reduce sanitary problems. The density is 2.5 m² / animal for females in collective pens and 1.8 m² / animal for gilts. It is recommended that extra attention be given to the question of regulating the amount of feed provided to females at the end of pregnancy and lactation. The sooner the pregnancy diagnosis is better, since the empty females are removed from the farrowing group. The study, through a literature review related to the welfare and management of swine pregnant women, helps by promoting proper procedures and warning about the undue for each situation, in order to reduce expenses, as well as improve the issue of animal welfare.